Lumped element circuit model approximation of an UWB patch antenna - Badjian M.H.; Chakrabarty C.K.; Devkumar S.; Hock G.C. (2023)
Simplified lumped element circuit model of an UWB patch antenna had been derived. The model was tuned based on the scattering parameter (S11) of the antenna structure obtained from the full electromagnetic simulator CST Microwave Office. The design uses FR-4 substrate with dielectric constant of 4.9 and thickness of 1.6 mm. Circuit model of such antenna is developed under AWR Microwave Office environment. Obtained results from the two simulators are then compared with the measured results. 2009 IEEE.